Farmer adaptation strategy in paddy field affected by climate variability in monsoon regions - APRIYANA, YAYAN; SARVINA, YELI; DEWI, ELSA RAKHMI; PRAMUDIA, ARIS (Asian Journal of Agriculture, 2017)
Apriyana Y, Sarvina Y, Dewi ER, Pramudia A. 2017. Farmer adaptation strategy in paddy field affected by climate variability in monsoon regions. Asian J Agric 1: 9-16. Adaptation of agriculture cultivation to climate variability and climate anomalies both in paddy field especially in monsoon regions is one of the strategies to minimize the impact of these two phenomena to reduce the economic loss, particularly for food security in Indonesia. The objectives of this study are: (i) to identify onset and cropping pattern in irrigated land, rainfed and dry land in affected area due to climate anomalies, (ii) to collect information on carrying capacity water resources and adaptation practices applied by farmers and, (iii) to identify strategies for farmers on irrigated land, rainfed and dry land in the region affected by climate variability. The desk work analysis and field survey were conducted in Serang District, Banten Province, Subang District, West Java Province and Pati District, Central Jawa Province, Indonesia. The study was undertaken in three cluster activities i.e. (i) correlation analysis of climate anomalies and rainfall, (ii) field survey and, (iii) analysis of onset planting season, cropping pattern, water availability, the best planting time and irrigation schedule. The results showed that the farmers in affected area due to climate variability could adapt by shifting the onset of planting season. Farmers in irrigated lands changed their onset around 2-4 ten-days period to October II - December II. Furthermore, in rainfed areas, the onset around 4-6 ten-days period was shifted to November I - January III. For dry land their onset around 6-8 ten-days period was moved to November II - February I. The cropping pattern rice-rice-palawija/fallow was applied on irrigated land. Furthermore, the pattern of rice-rice/palawija/fallow-fallow was carried out in rainfed. Finally, the pattern of palawija-palawija/fallow-dormant was performed on the dry land. Adaptation programs dealing with climate variability in Serang and Pati Districts varied more than in Subang District. In Serang and Pati, during the first planting season, farmers applied irrigation roughly 20%-30% of water pump from the river and during second planting season, farmers in Pati District used water from well-pump, as well as in Serang that can reach 100% of the application.